SYEKH MOHAMMAD ARSYAD THAWIL 1851-1934 : PERJUMPAAN ULAMA BANTEN DENGAN JEMAAT KRISTEN MINAHASA - Almunauwar Bin Rusli (Balai Penelitian dan Pengembangan Agama Makassar, 2020)
The fight of Ulama in the history of Indonesian colonialism took place through eschatological awareness, ethical action and mystical reflection. Syeikh Mohammad Arsyad Thawil is one of the important Ulama in this case. He was born in Tanara, Banten 1851 and died in Lawangirung, Manado 1934. Syekh Mohammad Arsyad Thawil studied Islam on three teachers: Syeikh Abdul Gani Bima, Syeikh Ahmad Zaini Dahlan and Syeikh Nawawi Al-Bantani. He lived in Makkah from 1868-1873 and was involved in the Banten peasant uprising 9-13 July 1888. First, since 1808 Banten fell under Dutch rule. Colonial bureaucracy destroys traditional bureaucracy. Second, abolition of inheritance, tax collection and forced labor. Third, the raises of sufi movements, pesantren and pilgrimage groups that formed the Pan-Islamic ideology. When exiled at Airmadidi, Minahasa 1888, the da’wah of Syeikh Mohammad Arsyad Thawil was supported by Kapiten Tan Tjin Bie. Thus, Islam and Tionghoa have relations of knowledge and power because of cooperation of commerce and memory of commerce.